Traumatic habitual dislocation of the personeal tendons - Moriwaki, N.; Omoto, H.; Kawamura, Y.; Senzoku, F. (Orthopedics & Traumatology, 1976)
Although traumatic habitual dislocation of the peroneal tendons is statistically uncommon, its occurrence can be expected to increase in frequency to parallel the rapid growth of skiing as a participant sport. There are already forty two cases in Japan. We recently experienced one case, had good effect by modified Dr. Vries' method.